Implementasi Uji Mann-Whitney pada Produksi Beras di Provinsi Kepulauan Bangka Belitung dan Provinsi Kalimantan Tengah - Ramadhani, Fitri (Scientia: Jurnal Hasil Penelitian, 2024)
Indonesia is an agrarian country so most of the population works as farmers and this is what makes agriculture has an important role in the national economy. Most of Indonesia's population uses rice as their staple food. Rice production in Bangka Belitung Islands Province in 2023 was 39.39 thousand tons, while rice production in Central Kalimantan Province was 198.84 thousand tons. The difference in rice production in Bangka Belitung Islands Province and Central Kalimantan can be analyzed using the Mann-Whitney Test. The purpose of this research is to find whether there is an average difference between rice yields in Bangka Belitung Islands Province and Central Kalimantan Province in 2023 using the Mann-Whitney Test. Based on the results of the analysis using the Mann-Whitney Test method manually and using SPSS 25, both tests draw the decision that H0 is accepted and H1 is rejected. Where manual data testing obtained Ucount≥Utable namely 34≥22 and for data testing using SPSS 25 obtained Asymp.Sig≥α namely 0,263≥0,05. So it can be said that the results of rice production in Bangka Belitung Islands Province and Central Kalimantan Province have no significant difference.